Findings of optical coherence tomography angiography of nasal optic disc hypoplasia - Miki Yoshimura; Yuki Hashimoto; Arisu Hatanaka; Takeshi Yoshitomi (American Journal of Ophthalmology Case Reports)
Purpose: This study aimed to present a case of a woman diagnosed with congenital nasal optic disc hypoplasia (NOH) in the right eye. Observations: A woman in her 20s presented with a small optic disc, irregular optic disc margins with a double-ring sign, and wedge-shaped defects temporally extending from Mariotte's blind spot in the right eye. The radial peripapillary capillary (RPC) density around the optic nerve disc was examined using optical coherence tomography angiography (OCTA). The best-corrected visual acuity was 1.2 OU, and intraocular pressure was 12 mmHg OU. Optical coherence tomography C-scan detected thinning of the circumpapillary retinal nerve fiber layer, and OCTA revealed that a decrease in RPC density on the nasal side of the optic disc in the right eye was markedly lower than that in the other eye areas. Furthermore, it was lower than the RPC density on the nasal side of the left eye. Conclusions and importance: OCTA may help detect the clinical features and pathogenesis of NOH.